Technology Policy: A Fixture on the National Agenda - Rycroft, Robert; Kash, Don; Adams, Richard (Maine Policy Review, 1995)
Federal government research and development priorities have shifted in recent years away from areas of national security and agency missions, and toward the enhancement of industrial competitiveness in the global economy. This shift has stirred ideological controversy over whether the federal government should be in the business of picking "winners" and "losers," even prompting some to label this practice “corporate welfare.” Rycroft, Kash, and Adams suggest that the central issues at stake have little to do with ideological differences and a great deal to do with whether the U.S.will continue to lead the world in technological innovation. They describe a new economic reality, driven by technology, that calls for basic changes to our national technology policy.
Keywords: technology policy